2020
DOI: 10.1186/s13643-020-01547-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of mechanical insufflation-exsufflation in invasively ventilated critically ill adults: a scoping review protocol

Abstract: Background Critically ill patients receiving invasive ventilation are at risk of sputum retention. Mechanical insufflation-exsufflation (MI-E) is a technique used to mobilise sputum and optimise airway clearance. Recently, interest has increased in the use of mechanical insufflation-exsufflation for invasively ventilated critically ill adults, but evidence for the feasibility, safety and efficacy of this treatment is sparse. The aim of this scoping review is to map current and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…[13][14][15] The scoping review protocol has been previously published. 16 There were no amendments made to the protocol during the conduct of the scoping review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] The scoping review protocol has been previously published. 16 There were no amendments made to the protocol during the conduct of the scoping review.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we did not exclude studies based on study design and did not restrict article selection based on language. 16 The search criteria were applied between January 1990-April 2021 using electronic databases MEDLINE, Embase, and CINAHL via the Ovid platform. PROSPERO and Cochrane Library were searched for relevant reviews, ISI Web of Science for conference abstracts, and the International Clinical Trials Registry Platform (trialsearch.…”
Section: Study Identificationmentioning
confidence: 99%
“…The search for predictors of extubation failure is a majortopic in ICU research. It is estimated that, among patients with prolonged ICU stay, about 85% have failed extubation, with a consequent increase in comorbidity and costs [9].Excess secretions has been lengthy recognized as an important factor in the outcome of extubation [10,11].Mokhlesiet al [12] wrote that the evaluation of endotracheal secretions, patient's mental state and pre-extubation PaCO2 could be used to predict extubation failure even in patients who had successfully passed a spontaneous breathing trial. In substantial agreement, Kulkarni et al [13] stated that the efficacy of coughing, the reduced amount of secretions and an adequate state of vigilance are necessary prerequisites for successful extubation, andSmina et al [14]reported that cough capacity, measured objectively, is a major predictor of extubationfailure.Other studiesunderlined that extubation failure is often mediated by an ICU-associated "acquired weakness", which is frequently observed in individuals undergoing prolonged mechanical ventilation and limits at the same time the ability to mobilize adequate air volumes through the lungs and to clear the airways through effective coughing [15].…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the respiratory muscles affects the outcome of extubation. Patients with a higher rate of failure in extubation often have insufficient respiratory muscle strength and weaker cough intensity [18,35]. There are many studies that use peak cough flow rate as the evaluation of cough intensity in MV patients and use it to predict the outcome of extubation [36].…”
Section: Discussionmentioning
confidence: 99%